Pelaksanaan MS 1900 (sistem pengurusan kualiti berasaskan syariah) dalam pengurusan hotel patuh syariah: Kajian di PNB Ilham Resort / Nor Azizah Tukiran - Nor Azizah , Tukiran (2018)
Shariah-Compliant Hotel Management is an area of management that is increasingly gaining public attention. The hotel management that meets the needs of the shariah is certainly an attraction to customers especially to Muslims. The most important aspects that are often emphasized are the proper management of halal and quality food and beverages provided by the hotel. At the same time, a few standards had already been issued by the Department of Standards Malaysia as guidelines for the hospitality industry namely MS 1900 (Shariah-based Quality Management System), MS 1500 (Halal Food: Production, Preparation, Handling and Storage) and MS 2610 (Hospitality Friendly Muslim). MS 1900, which is a standard of shariah based quality management, is seen to be less welcome among hoteliers. However, PNB Ilham Resort as one of the PNB hotel chains, is seen to be committed to continuously adopting MS 1900. It is therefore interesting for the researcher to study the implementation of MS1900 at PNB Ilham Resort. Hence, this study outlines four objectives of the study. First, is to analyse MS 1900 content and its suitability to be applied in sharia-compliant hotel management; Second, is to study MS1900 compliance activities in food and beverage management at PNB Ilham Resort; Third, is to identify the MS 1900 implementation challenges; and Fourth is to study the impact of the MS 1900 implementation at PNB Ilham Resort. Qualitative approach has been used to achieve the four objectives of this study. Semi-structural interview, observation and documentation analysis were conducted to obtain data. The findings of this study showed that the strength of MS 1900's lies on a more comprehensive summarization in order to create a holistic and quality shariah-compliant hotel management systems. The study also found five main ivities in ensuring MS 1900 compliance were conducted at PNB Ilham Resort, systematic shariah-compliant documentation, management involvement, shariah compliance in clear work operations, orderly shariah-compliant resource management and internal and external surveillance audit. In addition, this study explains the various forms of challenges and impacts that need to be addressed wisely to implement MS 1900. Overall, this study finds the appropriate standards for managing the shariah compliant hotel based on the experience at PNB Ilham Resort. It is hoped that the implementation of MS 1900 at PNB Ilham Resort will be a useful reference and adopted by other hotel management. Keyword: